2005
DOI: 10.4049/jimmunol.174.11.7440
|View full text |Cite
|
Sign up to set email alerts
|

Initial High-Dose Nasal Allergen Exposure Prevents Allergic Sensitization to a Neoantigen

Abstract: Primary allergic sensitization—IgE formation after Ag exposure—is fundamental in the development of allergic respiratory disease. With the rising prevalence of asthma and allergic rhinitis, improved understanding of the determining factors for allergic sensitization is needed. Human epidemiologic studies suggest high-dose allergen exposure may paradoxically protect against sensitization. Prospective human studies of allergen dose effect on primary allergic sensitization are lacking. We prospectively examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…It should be noted that exposure to a higher dose (i.e., 1 mg DEP) did not induce an increased IgE response (Diaz-Sanchez et al, 1994), which could be due to inherent toxicity and/or paradoxical protection due to a high allergen dose (Riedl et al, 2005). Because DEPs are composed with dissimilar physicochemical properties, the possibility exists that responses (related to immune and inflammatory changes) may be qualitatively or quantitatively different, depending on which properties are involved in the response.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that exposure to a higher dose (i.e., 1 mg DEP) did not induce an increased IgE response (Diaz-Sanchez et al, 1994), which could be due to inherent toxicity and/or paradoxical protection due to a high allergen dose (Riedl et al, 2005). Because DEPs are composed with dissimilar physicochemical properties, the possibility exists that responses (related to immune and inflammatory changes) may be qualitatively or quantitatively different, depending on which properties are involved in the response.…”
Section: Discussionmentioning
confidence: 98%
“…7 Our data support the hypothesis that airways allergy, both asthma and allergic rhinitis, results from failure to tolerize actively the airway mucosal immune system early in life through antigen stimulation. 26,31,32 If the early response is not appropriately directed, subsequent mucosal contact with innocuous aeroallergens results in allergic sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic emissions such as diesel exhaust particles have an impact on the immune system and promote a Th2-dominated immune response [7]. Furthermore, it was shown that diesel exhaust particles can prime the immune system to develop a neoantigen proallergenic immune response with high levels of allergen-specific IgE [8, 9]. …”
Section: Introductionmentioning
confidence: 99%